Analisis Rebranding Produk Kecantikan Lokal “Luxcrime” pada Perkembangan Brand - Effendy, Valerie (Wimba : Jurnal Komunikasi Visual, 2024)
Local beauty products such as Viva, Purbasari, Sariayu, and Mustika Ratu have been present since the 1960s, but their branding has primarily targeted adults. However, since the 2010s, there has been a growing development of local beauty products specifically for teenagers. The peak of this trend occurred during the pandemic, as teenagers became more conscious of self-care, resulting in significant growth for local beauty brands like Luxcrime. This research aims to analyze the relationship between Luxcrime's rebranding and its progress in the Indonesian beauty industry before and after the pandemic. The study employs qualitative methods of visual content analysis and descriptive analysis to examine Luxcrime's re-branding from the perspective of Conceptual Branding Theory and Brand Equity. The findings indicate that Luxcrime’s rebranding has a significant impact on brand advancement by creating opportunities for product expansion and expanding market share through the introduction of new visual elements.